2009
DOI: 10.1063/1.3081047
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-controlled and diffusionless crystal growth in liquid o-terphenyl near its glass transition temperature

Abstract: o-terphenyl is one of the organic liquids in which a fast mode of crystal growth is activated near the glass transition temperature T(g) and continues deep in the glassy state. This growth mode, termed glass-crystal (GC), is not limited by molecular diffusion in the bulk liquid, in contrast to the diffusion-controlled growth at higher temperatures. The GC mode has been previously described as abruptly emerging near T(g) and having a constant growth rate at a fixed temperature, two features important for testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 28 publications
8
59
0
Order By: Relevance
“…After the temperature is returned to 267 K, new GC growth was initiated predominately on the tips of the actively growing, far-reaching fibers. Xi et al reported a similar observation for GC growth in OTP (30).…”
Section: Gc Growth Has Precursor In the Equilibrium Liquidsupporting
confidence: 63%
“…After the temperature is returned to 267 K, new GC growth was initiated predominately on the tips of the actively growing, far-reaching fibers. Xi et al reported a similar observation for GC growth in OTP (30).…”
Section: Gc Growth Has Precursor In the Equilibrium Liquidsupporting
confidence: 63%
“…Thus, as previously postulated, negligible bulk molecular motion at temperatures well below T g cannot guarantee the stability of amorphous solids. Moreover, in addition to surface crystallization, diffusionless glassy crystal growth has also been documented in several organic systems near and below T g (20)(21)(22). These modes of crystallization cause a sudden increase in crystallization rate near or below T g compared to the crystallization rate from the supercooled liquid.…”
Section: Significance Of Surface Crystallization For the Stability Ofmentioning
confidence: 95%
“…One such growth mode (the glass-to-crystal or GC mode) exists in the bulk and can cause an increase of crystal growth rate by orders of magnitude with a temperature drop by a few K (6)(7)(8)(9)(10). Another growth mode occurs at the surface and can lead to crystal growth substantially faster at the surface than in the interior (11)(12)(13)(14); this surface growth mode can be halted by a coating only a few nm thick (12).…”
Section: Introductionmentioning
confidence: 97%